Tungsten trioxide/zinc tungstate bilayers: electrochromic behaviors, energy storage and electron transfer (2014)
ABSTRACT: Pair-sequentially spin-coated tungsten trioxide (WO3) and zinc tungstate (ZnWO4) bilayer films onto indium tin oxide (ITO) coated glass slides have been prepared via sol-gel methods followed by annealing. The bilayers (ZnWO4/WO3 denoting the bilayer film with the inner layer of ZnWO4 and the outer layer of WO3 on the ITO while WO3/ZnWO4 standing for the bilayer film with the inner layer of WO3 and the outer layer of ZnWO4 on the ITO) exhibit integrated functions of electrochromic and energy storage behaviors as indicated by the in situ spectroelectrochemistry and cyclic voltammetry (CV) results. Accordingly, blue color was observed for the bilayer films at -1 V in 0.5 M H2SO4 solution. An areal capacitance of 140 and 230 F/cm2 was obtained for the ZnWO4/WO3, and WO3/ZnWO4 film, respectively, at a scan rate of 0.05 V/s in the CV measurements. The CV results also unveiled the electron transfer behavior between the semiconductor films in the oxidation process, suggesting a sequence-dependent electrochemical response in the bilayer films. Meanwhile, methylene blue (MB) was used as an indicator to study the electron transfer phenomenon during the reduction process at negative potentials of -0.4 and -0.8 V, in 0.5 M Na2SO4. The results indicated that the electrons transfer across the bilayers was enhanced at more negative potentials.